PENGARUH KOMUNIKASI PEMASARAN DAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI PT. FURNILUX INDONESIA - Handoko Syahputra Salim; Thomas Sumarsan Goh; Errie Margery (STIE-PMCI, 2022)
PT. Furnilux Indonesia is a company that runs in the field of services where the goods offered are furniture or more precisely items related to household equipment such as: chairs, tables, wardrobes, decorative cabinets and others. Companies rarely communicate to consumers so consumers rarely know the existence of PT. Furnilux Indonesia and the company are very out of date in communicating its products to consumers. Consumers complained about the product motives that were laughing to consumers not in accordance with what was promised. The purpose of this study was to analyze the effect of marketing and product communication on purchasing decisions at PT. Furnilux Indonesia.The population in this study are consumers at PT. Furnilux Indonesia, located in Medan, North Sumatra, 125 people began in March 2020 – June 2020. So the sample of this study was 95 respondents. Data collection techniques used are: questionnaire, questionnaire, library research. Analysis of the data used in this study is multiple linear regression analysis.The results showed that marketing communication partially affected purchasing decisions at PT. Furnilux Indonesia. Partially, the product affects the Purchasing Decision at PT. Furnilux Indonesia. Simultaneously marketing communication and product influence on purchasing decisions at PT. Furnilux Indonesia.